Monolayer thermal meta-device with switching functions. (1st May 2022) - Han, Tiancheng; Yue, Xiuli; Wen, Kaihuai; Nangong, Junyi
Highlights: Transformation theory has provided a novel design methodology allowing a plethora of unprecedented metamaterials, e.g., path-dependent metamaterials that simultaneously possess multiple distinct functions. However, transformation-based metamaterials commonly come along with anisotropic, inhomogeneous, and extreme parameters, resulting in big challenges on their experimental realization and performance. Here, we propose a monolayer thermal meta-device that functions as an invisible sensor or cloak when heat flows under different directions. This is achieved based on scattering cancelling method by employing only one layer of bulk isotropic materials, which drastically facilitate feasible realization and fabrication. The anisotropic functionality is experimentally confirmed in both steady state and time-dependent case, which demonstrates an excellent thermodynamic performance. Our approach may inspire new alternatives to the functionalities promised by transformation optics. Due to the exact design, convenient implementation, and excellent performance, this work may provide a new route for designing of multifunctional meta-devices in the Laplacian and wave-dynamic fields. We believe that this work fits well within the scope of Int. J. Heat mass Tran., and the journal will be an excellent vehicle for the dissemination of this work. Abstract: Transformation theory has provided a novel design methodology allowing a plethora of unprecedented metamaterials, e.g., path-dependent metamaterials that simultaneously possess multiple distinct functions. However, transformation-based metamaterials commonly come along with anisotropic, inhomogeneous, and extreme parameters, resulting in big challenges on their experimental realization and performance. Here, we propose a monolayer thermal meta-device that functions as an invisible sensor or cloak (in which the sensor is wrapped by an insulating layer) when heat flows under different directions. This is achieved based on scattering cancelling method by employing only one layer of bulk isotropic materials. The switching functions are experimentally confirmed in both steady state and time-dependent case, which demonstrates an excellent thermodynamic performance. Due to the exact design, easy implementation, and excellent performance, this work may provide a new route for designing of meta-devices with switching functions in the Laplacian and wave-dynamic fields.